Evaluation of probe-based ultra-sensitive detection of miRNA using a single-molecule fluorescence imaging method: miR-126 used as the model - Liu, Longkai; Wang, Xiaoning; Li, Yan; Liu, Jianwei (Frontiers in Bioengineering and Biotechnology, 2023)
This study proposed a new detection method of miRNA based on single-molecule fluorescence imaging, a method that has been successfully developed to measure the light signal of individual molecules labeled with proper fluorophores. We designed probes 1 and 2 to be labeled with Cy5 dye and BHQ2 quencher at the 3′ terminals, respectively. Probe 1 consisted of two parts, the longer part complementary to miR-126 and the shorter part complementary to probe 2. After hybridization, miR-126 bound to probe 1 by replacing probe 2 and assembled into a double-stranded DNA with probe 1. The abundance of miR-126 was quantified by detecting image spots of Cy5 dye molecules from probe 1/miR-126 complexes. MiR-126 single-molecule imaging method showed high specificity and sensitivity for miR-126 with a detection limit of 50 fM. This method has good selectivity for miR-126 detection with 2.1-fold, 8.8-fold, and 26.9-41.3-fold higher than those of single-base mismatched miR-126, three-base mismatched miR-126 and non-complementary miRNAs (miR-221, miR-16, miR-143 and miR-141). The method to detect miR-126 was validated in breast cancer cell lines. Our single-molecule miRNA imaging showed high specificity and sensitivity for miRNAs. By changing the base pair sequence of the designed probes, our method would be able to detect different miRNAs.